2018
DOI: 10.1038/s41598-018-34349-z
|View full text |Cite
|
Sign up to set email alerts
|

Turning date palm fronds into biocompatible mesoporous fluorescent carbon dots

Abstract: Here, we demonstrate the synthesis of mesoporous carbon dots (Cdot) from date palm fronds and their excellent excitation wavelength-independent photoluminescence (PL), with high photo- and storage-stability, superior biocompatibility and thermal and electrical conductivity for the first-time by a simple, green, one-step carbonization method. Interestingly, the as-obtained Cdot manifest the spherical shape of about 50 nm average diameter having surface mesopores of size less than 10 nm with sp2 hybridized carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 52 publications
(31 reference statements)
1
43
0
Order By: Relevance
“…Almost the same spectra were observed for all of the sources. A broad peak at ~ 3300 cm −1 was related to hydroxyl groups stretching vibrations [26,27]. A peak appeared at ~ 2930 cm −1 represent the C-H stretching bond as a main characteristic bond for CQDs [50].…”
Section: Characterization Of Cqdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost the same spectra were observed for all of the sources. A broad peak at ~ 3300 cm −1 was related to hydroxyl groups stretching vibrations [26,27]. A peak appeared at ~ 2930 cm −1 represent the C-H stretching bond as a main characteristic bond for CQDs [50].…”
Section: Characterization Of Cqdsmentioning
confidence: 99%
“…For example, CQDs prepared by chitosan (as a precursor) are used in the manufacture of electronic devices [25]. Quantum dots synthesized using glucose and tree date palm are other examples of green synthesis of CQDs that have been used for the biological imaging in the body of living things [26] and luminous diodes respectively [27]. Recently, Yang et al, reported the preparation of high-fluorescence-doped quantum dots from glucose and showed their application in the detection of cancer cells in mice [28].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Although many of the aforementioned synthesis methods can be found in the literature, hydrothermal treatment in either a top-down or bottom-up regime is most commonly employed. In particular, this method is favored amongst reports of carbon dot “green syntheses” from biomass, or natural precursors [ 17 , 22 , 48 , 49 ].…”
Section: Characterization Of Carbon Nanodots: An Overview Of Key Smentioning
confidence: 99%
“…In addition to the antibacterial effects that will be discussed in the subsequent section, ROS detected from carbon dots and related graphene quantum dots have also been noted to cause lipid peroxidation [ 25 ], depletion of antioxidants in cells [ 25 ], and even to a degree dye degradation [ 49 ]. The secondary effects of ROS generated by carbon dots remain to be further elucidated and should persist as a consideration from both a fundamental and experimental perspective for future carbon dot APDT investigations.…”
Section: Carbon Nanodots As Photodynamic Antimicrobial Agentsmentioning
confidence: 99%
“…[16][17][18][19][20] In this regard, various carbon-rich resources have been employed as single precursors for the production of CDs. [21][22][23] However, the latter show weaker PL compared to those from dual precursors. Doping CDs with non-metal moieties such as N dopants has been considered as the most promising approach to QY enhancement by tuning the upward shi of the Fermi level.…”
Section: Introductionmentioning
confidence: 98%